Cold case Christmas - Patch, Jessica R. (Love inspired suspense., 2018)
Home for Christmas after her long-missing mother's body is found, nothing will keep Nora Livingstone from uncovering the truth about the cold case. Especially not Deputy Sheriff Rush Buchanan, whom she once loved and left. Even when threats become attempts on her life, Rush can't dissuade her--but he will protect her. Because someone is determined to bury the truth...or bury Nora.